APLIKASI PLATFORM WEB KOPERASI SIMPAN PINJAM MENGGUNAKAN FRAMEWORK CODEIGNITER DENGAN METODE SCRUM ( Studi Kasus : Koperasi Tani Makmur ) - Muhammad Amirudin; Hadi Sucipto; Tanhella Zein Vitadiar; Mahrus Ali (Fakultas Teknologi Informasi, 2025)
Cooperatives are one of the driving forces of the Indonesian economy, but often face the problem of a lack of information on customer deposits and loans that exceed the specified amount. Research conducted at the Makmur Farmers Cooperative, Tejo Village, Mojoagung District monitor functioning collaborative systems. Online platform applications can be used in collaborative processes. A web-based application created with the Codeigniter framework using the Scrum method, which aims to minimize the occurrence of problems in the collaborative savings and loan process. The Scrum method is often used because it implements processes in short iterative cycles and actively involves users in post-creation, prioritization, and review. This research aims to design and build an application capable of handling savings, loans and repayment. From the results of the training survey on developing the Savings and Loans Application System for Rich Farmer Cooperatives, it was found that 5 respondents agreed to use information technology to assist and develop the work of the Savings and Loans Cooperative application. Keyword : Cooperatives. SCRUM method, deposits and loans